Analysis of Industrial Carbon Transfer in Beijing-Tianjin-Hebei City Cluster and Surrounding Areas - Siqin, Gao; Huijuan, Wang (Frontiers in Environmental Science, 2022)
Under the emission reduction pressure to win the blue-sky defense battle in 2020, the environmental situation in Beijing-Tianjin-Hebei and surrounding areas is still grim, and the optimization of its industrial structure and the adjustment of its energy structure are imminent. With the rapid development of interregional trade in intermediate products, carbon emissions are transferred across regions with the trade. Due to the large differences in the technology, industrial structure, and economic development of cities, extending the environmental governance chain of Beijing-Tianjin-Hebei and surrounding areas is indispensable. In this context, based on the interregional input-output tables in 2002, 2007, and 2012, we establish an average propagation length (APL) model and a structural path analysis model (SPA) model for the carbon conduction relationship in the Beijing-Tianjin-Hebei region compared with the Yangtze River Delta and the Pearl River Delta. The results show that: i) From the perspective of carbon-related industries outside the urban clusters, the main reason for the low carbon transfer efficiency of the Beijing-Tianjin-Hebei is the insufficiency of related industries. During the study period, the Beijing-Tianjin-Hebei urban clusters mainly used the electricity and heat department as an intermediary to transfer carbon-containing resources from various industries in resource provinces; ii) From the perspective of the transfer of industrial structure within the urban clusters, the tertiary industry in Hebei Province still has great development potential. During the study period, the total amount of carbon transferred from the tertiary industry of Hebei Province to Beijing and Tianjin has always remained at the same level, while other resource provinces have increased significantly; iii) From the perspective of carbon transfer in specific industrial sectors, the excessively high thermal carbon emission coefficients of Shanxi and Inner Mongolia are the main reasons for the large amount of redundant carbon generated in the Beijing-Tianjin-Hebei region.